Imagining Outside of a Pandemic: A Response from a Queer Improvising Percussive Dancer - Gareiss, Nic (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
I'm a dancer who engages improvisation every time I put on my shoes to brush, step, click, and knock the floor. Not surprisingly, my work until March 2020 was primarily with fellow sound-makers, usually folk musicians from Ireland, Scotland, what's now called Canada, and what's now called Appalachia. COVID-19 has forced me to listen to the extemporaneous music I make anew, in the absence of collaborators, within a soundscape of profound uncertainty. In this contribution, I offer a voice from the floor, enunciated by my lowest limbs contacting the surface upon which I stand. This is where my work as an LGBTQ2IA+ improvising step dancer finds its meaning. In this essay, I respond to the incisive queer horizon Thomas F. DeFrantz casts, as "imagining outside of what came before." I share ways I have been thinking about improvisation and offer thoughts on how we might learn from DeFrantz to imagine and improvise “outside of” critically, queerly, and generatively.